HUBUNGAN AKTIVITAS DAN PEMANFAATAN SARANA BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATERI PELAJARANSENI RUPA DI SMA N 1 JUNJUNG SIRIH KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK - LENI MARLINA, Drs. Eswendi, M.Pd, Dra. Zubaidah A, M.Sn (Serupa The Journal of Art Education, 2014)
This studyaims to describethe relationshipof learningactivitiesandthe utilization oflearningwiththe learning outcomesof studentsof SMA Negeri1JunjungSirihSubdistrict ofJunjung Sirih Solok. This research iscorrelational research. Samples were takenusingpurposive random sampling technique. Data was collectedby distributing question naires directlyto the students whoelected tosample. Ifthe datain the descriptive and correlational techniques. From theresults ofthis study concluded thatthere is asignificant relationshipbetween: 1) learning activitiestostudent learning outcomes, 2) the use ofa means of learningwithstudent learning outcomes, 3) theuse oflearning activitiesandlearning toolswithfine artsstudentslearning outcomesSMA Negeri 1 Junjung Solok.